Pengaruh Mekanisme Good Corporate Governance, Kinerja Keuangan, dan Kualitas Audit Terhadap Ketepatan Waktu Pelaporan Keuangan: Studi Pada Perusahaan Manufaktur - Nabila Tamara Gufranita; Ayu Noviani Hanum; Nurcahyono Nurcahyono (Universitas Muhammadiyah Semarang, 2022)
This study aims to determine the effect of independent commissioners, audit committees, profitability, solvency, and audit quality on the timeliness of financial reporting in manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The population in this study are basic industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. This research uses purposive sampling technique. The sample used in this study were 62 manufacturing companies in the basic and chemical industry sectors listed on the Indonesia Stock Exchange during the period 2019-2021, so that based on the predetermined criteria, the total number of samples was 186 samples. The analysis used in this study islogistic regression analysis using SPSS version 25 as a tool for calculations. Based on the results given in this study, it shows that profitability and solvency have a negative effect on the timeliness of financial reporting while independent commissioners, audit committees and audit quality have no effect on the timeliness of financial reporting. The predictive ability of the five variables on the timeliness of financial reporting is 33.8%, while the other 66.2% comes from other variables.Keywords: independent commissioner; audit committee; profitability; solvency; and timeliness of financial reporting